Direct and indirect effects of emotional intelligence on depression and life satisfaction: Two sequential path-analysis approaches through perceived stress and symptoms of eating disorders. - Peláez-Fernández, María Ángeles; Extremera-Pacheco, Natalio; Mills, Jennifer S. (My University, 2024)
Past studies have confirmed that emotional intelligence (EI) is a key personal factor for preventing depressive symptoms and increasing life satisfaction, as well as in decreasing perceived stress and symptoms of eating disorders (ED). Similarly, research has showed that perceived stress and symptoms of ED are positively associated to depression and negatively associated to life satisfaction. However, no prior studies have yet tested the multiple intervening roles of both perceived stress and ED symptoms as potential mediators of the association between EI and depression/life satisfaction. The present study aims to bridge these gaps by testing a sequential path model. Specifically, we examine the potential sequential mediation effects of perceived stress-ED symptoms on the link between EI and depression and life satisfaction. A sample composed of 923 Spanish graduate students and community adults completed measures of EI, perceived stress, life satisfaction, depressive symptoms and ED symptomatology. The results show that high levels of EI were negatively associated with perceived stress, ED symptoms and depression; and positively associated with life satisfaction. Perceived stress and ED symptoms were positively associated to depressive symptoms, and negatively linked to life satisfaction. Moreover, path analyses showed that perceived stress and ED symptoms partially mediated the relationship between EI and depression and life satisfaction in sequence. These findings suggest that EI plays a key role in reducing symptomatology of depression and increasing life satisfaction through decreased perceived stress and ED symptomatology, providing novel evidence regarding psychological mechanisms through which EI contributes to a reduction of depression and increase of life satisfaction. Implications for assessing and improving these psychological resources in ED preventive programs are discussed.
Keywords: Madurez afectiva; Depresión mental; Estrés (Psicología); Conducta alimentaria - Trastornos; Emotional intelligence; Life satisfaction; Depression; Perceived stress; Eating disorders